Long-service-life low-temperature-resistant lead-acid storage battery negative electrode lead paste and production process thereof

By adopting a specific formula of long-life low-temperature negative electrode lead paste in lead-acid batteries, combined with ball milling and airflow ultrafine crushing technology, the problem of poor function of the negative electrode expansion agent in low-temperature environments is solved, and the cycle life and low-temperature discharge performance of the battery are significantly improved.

CN119812228APending Publication Date: 2025-04-11TIANNENG BATTERY GRP (JIANGXI) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510001390.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively extend the cycle life and discharge time of lead-acid batteries in low temperature environments, especially when the expansion agent of the negative electrode plate is not effective.

Method used

A long-life low-temperature resistant lead acid battery negative electrode lead paste is adopted, which includes precipitated barium sulfate, humic acid, lignin, superconducting carbon black, thermally cracked carbon black, expanded graphite and mixed paste acid, and the expansion agent is uniformly distributed through ball milling and airflow ultrafine crushing processes, and expanded graphite is added through fire to improve its structure and performance.

Benefits of technology

The uniform distribution of the negative electrode expansion agent in the lead paste is achieved, fine lead sulfate particles are generated, the crystals are avoided, and the high specific surface area after multiple cycles of the negative electrode are maintained, the distribution and performance of expanded graphite is improved, and the low-temperature performance and cycle life of the battery are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812228A_ABST
    Figure CN119812228A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of storage battery production, and discloses a long-life low-temperature-resistant lead-acid storage battery negative electrode lead plaster, which ensures the uniform distribution of a negative electrode expanding agent in the lead plaster, ensures the generation of fine lead sulfate particles during discharging, and avoids the growth of lead sulfate crystals, thereby ensuring that a negative electrode still has a very large specific surface area after multiple cycles. Expanded graphite is added through a pyrogenic process, the temperature reaches about 1500 DEG C, the volume of the expanded graphite reaches 200-300 times of the initial volume, it is guaranteed that the expanded graphite is evenly distributed in the lead paste, the wormlike graphite is loose in structure, bent due to multiple control, enlarged in surface area, improved in surface energy and enhanced in adsorption capacity, and the wormlike graphite can be automatically embedded, so that the lead paste is formed. And the flexibility, rebound resilience, conductivity and plasticity are improved. The coated free lead has a larger specific surface area, and the performance of the battery is greatly improved by utilizing the conductivity of carbon in the later stage of discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention and the technical field of battery production, in particular, relate to the field of battery production for electric bicycles, specifically to a long-life, low-temperature-resistant lead-acid battery negative electrode lead paste and a production process thereof. Background Art

[0002] Electric bicycles have become an important means of transportation. From a market perspective, users are most concerned about the battery life and how far they can travel on a single charge. In winter, when the temperature drops below 0°C, the range of electric vehicles is greatly reduced. Many electric vehicles that can run 50 kilometers in summer can only run more than 20 kilometers in winter. Many customers have developed bad usage habits, such as charging the battery after it is completely used up, or charging it after riding for a few days. These usage habits that cause deep discharge of the battery affect the battery life.

[0003] The key factor affecting the cycle life and low-temperature discharge time of electric vehicle batteries lies in the negative plate.

[0004] Each time the battery is charged and discharged, the active material undergoes a process of contraction and expansion. The negative electrode active material is a sponge-like free state of metallic lead with a large specific surface area. At the end of discharge, it becomes lead sulfate and expands by 164%. During the discharge process, the PbSO4 generated by lead oxidation quickly covers the surface of NAM, greatly reducing the capacity of NAM. The deep NAM terminates the reaction because it cannot get sulfuric acid. In order to reduce the passivation effect of NAM caused by the PbSO4 layer, engineers from various countries are studying negative electrode expanders, so that 20%-50% of the negative electrode active material participates in the oxidation reaction. The organic expander sodium lignin sulfonate, as a surface active polymer, adsorbs to the lead surface to prevent the formation of a continuous PbSO4 passivation layer. The inorganic expander barium sulfate provides crystal nuclei to generate a large number of tiny PbSO4 crystals, forming a porous but non-continuous PbSO4 layer, so that not only the surface of the negative electrode active material can participate in the discharge reaction. When most of the lead is oxidized to lead sulfate, carbon can conduct current, so these three traditional negative electrode expanders are indispensable for lead-acid batteries.

[0005] Research in the past two years has found that, from the perspective of battery failure modes, although the apparent failure modes are corrosion of the positive plate grid and mudification of the positive lead paste, the key reason for the end of life lies in the negative electrode. A large part of the reason is that traditional negative electrode additives and their production processes cannot play the role of expansion agents well, especially in low temperature environments and deep discharge recovery.

[0006] The patent with publication number CN108598472A discloses a low-temperature resistant lead paste for negative electrode of lead-acid battery, which is composed of lead powder, negative electrode additive, water and paste acid. The negative electrode additive comprises 0.5-1.0 parts of strontium sulfate or barium sulfate, 0.1-0.15 parts of sodium lignin sulfonate, 0.4-0.8 parts of humic acid and ethanoic acid based on 100 parts of lead powder by weight.

[0007] 0.3-0.6 parts, synthetic agent 0.6-1.2 parts, carbon nanotubes 0.1-0.2 parts, nano Kejen black 0.05-0.1 parts, conductive carbon fiber 0.1-0.15 parts, sodium hydroxymethyl cellulose 0.1-0.5 parts.

[0008] The battery produced by the above scheme has good initial low-temperature performance, but poor cycle life. The failure mode is manifested as corrosion of the positive electrode grid. The possible reason is that after 100 cycles, lignin is precipitated, the negative electrode hydrogen evolution overpotential is reduced, and the cathode absorption capacity is reduced. When charging too quickly, it is fully charged, resulting in insufficient charging of the positive electrode and over-discharge of the positive electrode during discharge.

[0009] How to make the negative electrode expansion agent play a long-term expansion role is the focus of technical research in the battery industry. Therefore, we need to propose a long-life, low-temperature resistant lead-acid battery negative electrode lead paste and its production process. Summary of the invention

[0010] The object of the present invention is to provide a long-life low-temperature resistant lead-acid battery negative electrode lead paste and a production process thereof, which ensures the uniform distribution of the negative electrode expansion agent in the lead paste, ensures the generation of fine lead sulfate particles during discharge, avoids the growth of lead sulfate crystals, and ensures that the negative electrode still has a very large specific surface area after multiple cycles; ensures the uniform distribution of expanded graphite in the lead paste, the worm-like graphite structure is loose, multi-controlled and curved, the surface area is enlarged, the surface energy is improved, the adsorption capacity is enhanced, and the worm-like graphite can be self-interlocked, which increases its flexibility, resilience, conductivity and plasticity. The free lead that is wrapped has a larger specific surface area, and the conductivity of carbon is utilized in the later stage of discharge, so that the performance of the battery is greatly improved to solve the problems raised in the above-mentioned background technology.

[0011] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a long-life low-temperature resistant lead-acid battery negative electrode lead paste, comprising the following raw materials, by mass percentage: 0.1-1wt% of precipitated barium sulfate, 0.2-0.6% of humic acid, 0.2-0.5% of lignin, 0.1-0.3% of superconductive carbon black, 0.1-0.3% of thermal cracking carbon black, 0.1-0.3wt% of expanded graphite, 7.8-8.5wt% of synthetic acid, 9-10wt% of formula water, 3-5wt% of recycled powder, 0.08-0.1wt% of short fibers, and lead powder with an oxidation degree of 73-79%.

[0012] Preferably, the raw materials are as follows, measured by mass percentage: 0.5-1wt% of precipitated barium sulfate, 0.2-0.5% of humic acid, 0.2-0.4% of lignin, 0.1-0.2% of superconductive carbon black, 0.2-0.3% of thermal cracking carbon black, 0.1-0.2wt% of expanded graphite, 7.8-8.5wt% of synthetic acid, 9-10wt% of formula water, 3-5wt% of recycled powder, 0.08-0.1wt% of short fibers, and lead powder with an oxidation degree of 73-79%.

[0013] Preferably, the raw materials are as follows, measured by mass percentage: 0.9wt% of precipitated barium sulfate, 0.25% of humic acid, 0.35% of lignin, 0.15% of superconductive carbon black, 0.25% of thermal cracking carbon black, 0.15wt% of expanded graphite, 8.2wt% of synthetic acid, 10wt% of formula water, 5wt% of recycled powder, 0.1wt% of short fibers, and lead powder with an oxidation degree of 73-79%.

[0014] Preferably, the content of the precipitated barium sulfate (on a dry basis) is ≥98.5%, the content of the humic acid is ≥90%, and the content of the ignition residue is ≤7%.

[0015] Preferably, the lignin is North American shortleaf pine lignin, the resistivity of the superconductive carbon black is 0.8-1.0 Ω.cm, and the nitrogen adsorption specific surface area of ​​the pyrolysis carbon black is 7-12 m2 / g.

[0016] Preferably, the recycled powder is lead paste powder obtained by crushing the scrapped negative electrode plates in the production process and passing through a 200-mesh sieve.

[0017] The present invention also provides a production process for a negative electrode lead paste for a long-life, low-temperature-resistant lead-acid battery, which is used to prepare the negative electrode lead paste for a long-life, low-temperature-resistant lead-acid battery described above, comprising the following steps:

[0018] S1. Mix 15 times the amount of precipitated barium sulfate, humic acid, lignin, superconductive carbon black and thermal cracking carbon black, place them in a ball mill, grind the formula materials at a speed of 20r / min for 2h, and then put the materials into the ultrafine grinding chamber. The high-speed rotating blades impact and crush the materials again. The airflow generated by the blades brings the materials to the grinding tank. The evenly mixed formula materials are packaged in 15 portions to obtain ingredient I;

[0019] S2, put 50% lead powder by weight into the paste machine, add ingredient I, slowly sprinkle the formula amount of expanded graphite on the paste machine platform, and use the outer flame of propane flame to blow the expanded graphite into the paste machine;

[0020] S3, adding the formula amount of recycled powder and short fibers, and then adding the remaining 50% by weight of lead powder, and dry mixing for 10 minutes;

[0021] S4, add formula water, the water adding time is 15S, wet stirring;

[0022] S5, adding the formulated amount of compounding acid into the compounding machine in 5 portions;

[0023] S6. Finally, stir for 10 minutes and control the specific gravity of the lead paste at 4.42-4.50g / cm3.

[0024] Preferably, in step S1, the diameter of the ball mill drum is 1.5 meters, 300 stainless steel balls with a diameter of 4 cm and 500 stainless steel balls with a diameter of 2 cm are installed inside the ball mill drum, and the rotation speed of the blade of the ultrafine grinding chamber is 23000 r / min.

[0025] Preferably, in step S2, the outer flame temperature of the propane gas combustion flame is controlled at 1500-1900°C.

[0026] Preferably, in step S5, during the process of adding the paste acid into the paste mixing machine, the maximum temperature of the lead paste is controlled at 55-60°C.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The present invention adopts North American shortleaf pine lignin to ensure the stability of lignin quality; the process method premixes the precipitated barium sulfate, humic acid, lignin, superconductive carbon black and thermal cracking carbon black in the formula amount and adopts the ball milling process and air flow ultrafine grinding method to ensure the uniform distribution of the negative electrode expansion agent in the lead paste, ensure the generation of fine lead sulfate particles during discharge, avoid the growth of lead sulfate crystals, and thus ensure that the negative electrode still has a very large specific surface area after multiple cycles;

[0029] 2. The present invention adds expanded graphite by pyrolysis, the temperature reaches about 1500℃, and the volume of expanded graphite reaches 200-300 times of the initial volume, which ensures the uniform distribution of expanded graphite in the lead paste. The worm-like graphite has a loose structure, is multi-controlled and curved, has an enlarged surface area, improved surface energy, enhanced adsorption capacity, and the worm-like graphite can be self-interlocked, which increases its flexibility, resilience, conductivity and plasticity. The free lead that is wrapped has a larger specific surface area, and the conductivity of carbon is utilized in the later stage of discharge, so the performance of the battery is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a flowchart of the present invention;

[0031] Figure 2 The cycle life curve of the lead-acid battery prepared in Example 1 of the present invention;

[0032] Figure 3The figure is a cycle life curve of the lead-acid battery prepared in comparative example. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the following examples and comparative examples, the manufacturing process of the positive plate is produced according to the normal process, and the positive grid alloy adopts the improved green alloy, whose main components are calcium 0.11-1.12%, tin 1.23-1.27%, aluminum 0.03-0.04%, lanthanum 0.0010-0.0015%, and the balance is metal lead. The formula of the positive plate lead paste is stannous sulfate 0.1-0.15%, antimony trioxide 0.11-0.12%.

[0035] Colloidal graphite 0.1-0.175%, Ketjen black 0.1-0.11%, 9-9.6% of 1.40g / cm3 of hydrated acid, 9-9.5% of pure water, and the rest is lead powder with an oxidation degree of 69%-73%. The positive plate grid adopts continuous casting and continuous punching process, and the weight of the grid small piece is 17g. The coating adopts continuous coating process, and after curing, the weight of the small positive plate is 91g-93g.

[0036] Example 1

[0037] See also Figure 1-2 The present invention provides a technical solution: a long-life low-temperature resistant lead-acid battery negative electrode lead paste, which comprises the following raw materials by mass percentage: 0.1-1wt% of precipitated barium sulfate, 0.2-0.6% of humic acid, 0.2-0.5% of lignin, 0.1-0.3% of superconductive carbon black, 0.1-0.3% of thermal cracking carbon black, 0.1-0.3wt% of expanded graphite, 7.8-8.5wt% of synthetic acid, 9-10wt% of formula water, 3-5wt% of recycled powder, 0.08-0.1wt% of short fibers, and lead powder with an oxidation degree of 73-79%.

[0038] Calculated by mass percentage, the raw materials include: 0.5wt% of precipitated barium sulfate, 0.2% of humic acid, 0.2% of lignin, 0.1% of superconductive carbon black, 0.2% of thermal cracking carbon black, 0.1wt% of expanded graphite, 7.8wt% of synthetic acid, 9wt% of formula water, 3wt% of recycled powder, 0.08wt% of short fiber, and lead powder with an oxidation degree of 73%.

[0039] The content of the precipitated barium sulfate (on a dry basis) is ≥98.5%, the content of the humic acid is ≥90%, and the content of the ignition residue is ≤7%.

[0040] The lignin is North American shortleaf pine lignin, the resistivity of the superconductive carbon black is 0.8-1.0 Ω.cm, and the nitrogen adsorption specific surface area of ​​the thermal cracking carbon black is 7-12 m2 / g.

[0041] The recycled powder is lead paste powder obtained by crushing the scrapped negative electrode plates in the production process and passing through a 200-mesh sieve.

[0042] The present invention also provides a production process for a negative electrode lead paste for a long-life, low-temperature-resistant lead-acid battery, which is used to prepare the negative electrode lead paste for a long-life, low-temperature-resistant lead-acid battery described above, comprising the following steps:

[0043] S1. Mix 15 times the amount of precipitated barium sulfate, humic acid, lignin, superconductive carbon black and thermal cracking carbon black, place them in a ball mill, grind the formula materials at a speed of 20r / min for 2h, and then put the materials into the ultrafine grinding chamber. The high-speed rotating blades impact and crush the materials again. The airflow generated by the blades brings the materials to the grinding tank. The evenly mixed formula materials are packaged in 15 portions to obtain ingredient I;

[0044] S2, put 50% lead powder by weight into the paste machine, add ingredient I, slowly sprinkle the formula amount of expanded graphite on the paste machine platform, and use the outer flame of propane flame to blow the expanded graphite into the paste machine;

[0045] S3, adding the formula amount of recycled powder and short fibers, and then adding the remaining 50% by weight of lead powder, and dry mixing for 10 minutes;

[0046] S4, add formula water, the water adding time is 15S, wet stirring;

[0047] S5, adding the formulated amount of compounding acid into the compounding machine in 5 portions;

[0048] S6. Finally, stir for 10 minutes and control the specific gravity of the lead paste at 4.42-4.50g / cm3.

[0049] The specific process of preparing the negative plate is as follows:

[0050] 1. First weigh 135kg of precipitated barium sulfate; 22.5kg of humic acid; 31.5kg of lignin; 13.5kg of superconductive carbon black; and 22.5kg of thermal cracking carbon black, add them into the designated ball mill, and ball mill for 2 hours. Then put the materials into the ultrafine grinding chamber, and the high-speed rotating blades will hit and crush the materials again. The airflow generated by the blades will bring the materials to the grinding tank, and the evenly mixed formula materials will be packaged into 15 portions to obtain ingredient I;

[0051] 2. Put 500kg of lead powder into the paste mixer and add 15kg of ingredient I from the observation port; hold the torch in your right hand, ignite it, grab a handful of expanded graphite with your left hand, slowly sprinkle it on the edge of the observation port, and use the torch to blow the expanded graphite into the paste mixer, adding a total of 1.5kg of expanded graphite; add 50kg of recycled powder and 1kg of short fiber at the observation port, and then add 500kg of lead powder with an oxidation degree of 73-79%, and dry mix and stir for 10 minutes.

[0052] 3. Add 97kg of formula water within 15S and stir wet for 6min; add 82kg of lead paste acid in 5 times, control the lead paste temperature at 58-60℃, and turn on the cooling water and circulating fan in time.

[0053] 4. Finally, stir for 15 minutes, and the paste temperature is 42-45℃;

[0054] 5. Coating, control the weight of the small plate after curing to 64-66g, and the weight of the small plate of the negative edge plate to 54-56g.

[0055] In step S1, the diameter of the ball mill drum is 1.5 meters, 300 stainless steel balls with a diameter of 4 cm and 500 stainless steel balls with a diameter of 2 cm are installed inside the ball mill drum, and the rotation speed of the blade of the ultrafine grinding chamber is 23000 r / min.

[0056] In step S2, the outer flame temperature of the propane gas combustion flame is controlled at 1500-1900°C.

[0057] In step S5, during the process of adding the paste acid into the paste mixing machine, the maximum temperature of the lead paste is controlled at 55-60°C.

[0058] Example 2

[0059] The same as Example 1 will not be repeated here, except that

[0060] The invention comprises the following raw materials by mass percentage: 0.9wt% of precipitated barium sulfate, 0.25% of humic acid, 0.35% of lignin, 0.15% of superconductive carbon black, 0.25% of thermal cracking carbon black, 0.15wt% of expanded graphite, 8.2wt% of synthetic acid, 10wt% of formula water, 5wt% of recycled powder, 0.1wt% of short fiber, and lead powder with an oxidation degree of 73-79%.

[0061] The specific process of preparing the negative plate is as follows:

[0062] 1. First weigh 135kg of precipitated barium sulfate, 30kg of humic acid, 45kg of lignin, 13.5kg of superconductive carbon black, and 22.5kg of thermal cracking carbon black, add them into the designated ball mill, ball mill for 2h, then put the materials into the ultrafine grinding chamber, the high-speed rotating blades will hit and crush the materials again, the airflow generated by the blades will bring the materials to the grinding tank, and the evenly mixed formula materials will be packaged into 15 portions to obtain ingredient I;

[0063] 2. Put 500kg of lead powder into the paste mixer, and add 16.4kg of ingredient I from the observation port; hold the torch in your right hand, ignite it, grab a handful of expanded graphite with your left hand, slowly sprinkle it on the edge of the observation port, and use the torch to blow the expanded graphite into the paste mixer, adding a total of 1.5kg of expanded graphite; add 50kg of recycled powder and 1kg of short fiber at the observation port, and then add 500kg of lead powder with an oxidation degree of 73-79%, and dry mix and stir for 10 minutes.

[0064] 3. Add 97kg of formula water within 15S and stir wet for 6min; add 82kg of lead paste acid in 5 times, control the lead paste temperature at 58-60℃, and turn on the cooling water and circulating fan in time.

[0065] 4. Finally, stir for 15 minutes, and the paste temperature is 42-45℃.

[0066] 5. Coating, control the weight of the small plate after curing to 64-66g, and the weight of the small plate of the negative edge plate to 54-56g.

[0067] Comparative Example

[0068] The specific process of preparing the negative plate is as follows:

[0069] 1. Put 500kg lead powder with an oxidation degree of 73-79% into the paste mixing machine, add 20kg normal negative electrode ingredient package, the components of the negative electrode ingredient package include: 9kg precipitated barium sulfate, 2.5kg Norwegian lignin, 3.5kg humic acid, 5kg acetylene black, add 1kg short fiber, then add 500kg lead powder, and dry mix for 10 minutes.

[0070] 2. Add 97kg of formula water within 15S and stir wet for 6min; add 82kg of lead paste acid in 5 times, control the lead paste temperature at 58-60℃, and turn on the cooling water and circulating fan in time.

[0071] 3. Finally, stir for 15 minutes, and the paste temperature is 42-45℃.

[0072] 4. Coating, control the weight of the small negative plate piece to 64-66g after the plate is cured, and the weight of the small negative plate piece to 54-56g.

[0073] The cycle life test of the lead-acid battery prepared by the comparative example is shown in Figure 3 .

[0074] The positive plates made by normal process, the plates obtained in Example 1, Example 2 and the comparative example are assembled into a 6-DZF-20F battery. The use scheme of the plates is shown in Table 1:

[0075] Table 1 Experimental design

[0076]

[0077]

[0078] The above schemes all use 4 positive plates, 3 negative plates, and 2 edge negative plates.

[0079] The finished batteries are tested for performance in accordance with the requirements of the standard "GB / T 22199.1-2017 Valve-regulated Lead-acid Batteries for Electric Power-Assisted Vehicles Part 1: Technical Conditions". Key indicators include 2hr capacity, high current discharge test, capacity retention rate, -18℃ capacity, fast charging capability, and cycle life test.

[0080] The specific test results are shown in Table 2:

[0081] Table 2 Test results of each scheme

[0082]

[0083]

[0084] As can be seen from the above table, the negative electrode lead paste and production process provided by the present invention have greatly improved the -18°C capacity and cycle life test performance. The increase in the amount of negative electrode active matter can effectively increase the low-temperature capacity. The key to the negative electrode formula of the present invention is the effective use of the negative electrode expansion agent, which ensures that the speed of contraction of the negative electrode specific surface area during the cycle is effectively controlled.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A long-life, low-temperature-resistant lead-acid battery negative electrode lead paste, characterized in that: The invention comprises the following raw materials by mass percentage: 0.1-1wt% of precipitated barium sulfate, 0.2-0.6% of humic acid, 0.2-0.5% of lignin, 0.1-0.3% of superconductive carbon black, 0.1-0.3% of thermal cracking carbon black, 0.1-0.3wt% of expanded graphite, 7.8-8.5wt% of synthetic acid, 9-10wt% of formula water, 3-5wt% of recycled powder, 0.08-0.1wt% of short fiber, and lead powder with an oxidation degree of 73-79%.

2. The long-life low-temperature resistant lead-acid battery negative electrode lead paste according to claim 1, characterized in that: The invention comprises the following raw materials by mass percentage: 0.5-1wt% of precipitated barium sulfate, 0.2-0.5% of humic acid, 0.2-0.4% of lignin, 0.1-0.2% of superconductive carbon black, 0.2-0.3% of thermal cracking carbon black, 0.1-0.2wt% of expanded graphite, 7.8-8.5wt% of synthetic acid, 9-10wt% of formula water, 3-5wt% of recycled powder, 0.08-0.1wt% of short fiber, and lead powder with an oxidation degree of 73-79%.

3. The long-life low-temperature resistant lead-acid battery negative electrode lead paste according to claim 1, characterized in that: The invention comprises the following raw materials by mass percentage: 0.9wt% of precipitated barium sulfate, 0.25% of humic acid, 0.35% of lignin, 0.15% of superconductive carbon black, 0.25% of thermal cracking carbon black, 0.15wt% of expanded graphite, 8.2wt% of synthetic acid, 10wt% of formula water, 5wt% of recycled powder, 0.1wt% of short fiber, and lead powder with an oxidation degree of 73-79%.

4. The long-life low-temperature resistant lead-acid battery negative electrode lead paste according to claim 1, characterized in that: The content of the precipitated barium sulfate is ≥98.5%, the content of the humic acid is ≥90%, and the content of the ignition residue is ≤7%.

5. The long-life low-temperature resistant lead-acid battery negative electrode lead paste according to claim 1, characterized in that: The lignin is North American shortleaf pine lignin, the resistivity of the superconductive carbon black is 0.8-1.0 Ω.cm, and the nitrogen adsorption specific surface area of ​​the thermal cracking carbon black is 7-12 m2 / g.

6. The long-life low-temperature resistant lead-acid battery negative electrode lead paste according to claim 1, characterized in that: The recycled powder is lead paste powder obtained by crushing the scrapped negative electrode plates in the production process and passing through a 200-mesh sieve.

7. A production process for a negative electrode lead paste for a long-life, low-temperature-resistant lead-acid battery, used for preparing a negative electrode lead paste for a long-life, low-temperature-resistant lead-acid battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Mix 15 times the amount of precipitated barium sulfate, humic acid, lignin, superconductive carbon black and thermal cracking carbon black, place them in a ball mill, grind the formula materials at a speed of 20r / min for 2h, and then put the materials into the ultrafine grinding chamber. The high-speed rotating blades impact and crush the materials again. The airflow generated by the blades brings the materials to the grinding tank. The evenly mixed formula materials are packaged in 15 portions to obtain ingredient I; S2, put 50% lead powder by weight into the paste machine, add ingredient I, slowly sprinkle the formula amount of expanded graphite on the paste machine platform, and use the outer flame of propane flame to blow the expanded graphite into the paste machine; S3, adding the formula amount of recycled powder and short fibers, and then adding the remaining 50% by weight of lead powder, and dry mixing for 10 minutes; S4, add formula water, the water adding time is 15S, wet stirring; S5, adding the formulated amount of compounding acid into the compounding machine in 5 portions; S6. Finally, stir for 10 minutes and control the specific gravity of the lead paste at 4.42-4.50g / cm3.

8. The production process of a negative electrode lead paste for a long-life low-temperature-resistant lead-acid battery according to claim 7, characterized in that: In step S1, the diameter of the ball mill drum is 1.5 meters, 300 stainless steel balls with a diameter of 4 cm and 500 stainless steel balls with a diameter of 2 cm are installed inside the ball mill drum, and the rotation speed of the blade of the ultrafine grinding chamber is 23000 r / min.

9. The production process of a negative electrode lead paste for a long-life low-temperature-resistant lead-acid battery according to claim 7, characterized in that: In step S2, the outer flame temperature of the propane gas combustion flame is controlled at 1500-1900°C.

10. The production process of a negative electrode lead paste for a long-life low-temperature-resistant lead-acid battery according to claim 7, characterized in that: In step S5, during the process of adding the paste acid into the paste mixing machine, the maximum temperature of the lead paste is controlled at 55-60°C.

Citation Information

Patent Citations

  • Low-temperature resistant negative lead paste of lead storage battery and preparation method of negative lead paste

    CN108598472A